2011
DOI: 10.1111/j.1600-0838.2009.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biological factors associated with a 24 h treadmill ultra‐marathon performance

Abstract: The purpose of this study was to examine the physiological and biological factors associated with ultra-endurance performance. Fourteen male runners volunteered to run on a treadmill as many kilometers as possible over a 24-h period (24TR). Maximal oxygen uptake (VO(2max)), velocity associated with VO(2max)(VO(2max)) and running economy (RE) at 8 km/h were measured. A muscle biopsy was also performed in the vastus lateralis muscle. The subjects ran 149.2 ± 15.7 km in 18 h 39 ± 41 min of effective attendance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
75
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 29 publications
11
75
0
1
Order By: Relevance
“…These chronic adaptations are in accordance with the acute power reduction verified after a 10-km running race (Gómez et al, 2002). The decrease in lower-limbs explosive power that was found in our study despite the negative effect on jumping performance wasn't reflected in running performance perhaps due to the increased mechanical efficiency provoked by alterations in gait pattern (Eriksson et al, 2011) or higher metabolic efficiency (Millet et al, 2011) induced by long-lasting workouts.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These chronic adaptations are in accordance with the acute power reduction verified after a 10-km running race (Gómez et al, 2002). The decrease in lower-limbs explosive power that was found in our study despite the negative effect on jumping performance wasn't reflected in running performance perhaps due to the increased mechanical efficiency provoked by alterations in gait pattern (Eriksson et al, 2011) or higher metabolic efficiency (Millet et al, 2011) induced by long-lasting workouts.…”
Section: Discussionsupporting
confidence: 73%
“…This is in accordance with our data which demonstrated running economy improvement with a significant reduction in muscle power. Besides higher mitochondrial oxidative capacity, performance in ultra-endurance events is mainly related to running economy (Millet et al, 2011), which corroborates the most significant physiological adaptations verified in this study. It seems that running economy improves independently of running intensity when running volume is significant (Enoksen et al, 2011), which was the main characteristic of the training protocol in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Davies and Thompson (Davies and Thompson, 1986) observed a linear increase of V · O2,max with time from the 50th to 240th minute during a 4 h race on a treadmill at constant speed, the rise becoming significant (P<0.01) after 110 min of exercise. In addition, the ability to maintain a high F over a 24 h treadmill run was found to be mainly related to a low CoT (Gimenez et al, 2013;Millet et al, 2011), and in the same study participants a significant change in running biomechanics, including higher oscillation frequency, lower vertical stiffness and lower ground reaction force (GRF), was observed . Indeed, interventions to reduce CoT are constantly sought by athletes, coaches and sport scientists.…”
Section: Introductionmentioning
confidence: 72%
“…The relationship between variables of physiology (Lazzer et al, 2011, Millet et al, 2011, cognition (Parry et al, 2011), anthropometry (Knechtle et al, 2010a(Knechtle et al, , 2010b, training (Knechtle et al, 2010a(Knechtle et al, , 2010b, pre-race experience (Knechtle et al, 2010a(Knechtle et al, , 2010b, gender (Lepers & Maffiuletti, 2011) and age ) with performance in ultra-endurance running competitions have been investigated. In 24-hours treadmill ultra-marathon performance, maximum oxygen uptake (VO2max) and the ability to run at a high %VO2max over time seemed to be the main physiological parameters correlated with better performance (Millet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In 24-hours treadmill ultra-marathon performance, maximum oxygen uptake (VO2max) and the ability to run at a high %VO2max over time seemed to be the main physiological parameters correlated with better performance (Millet et al, 2011). Furthermore, it appeared that anthropometric characteristics such as body mass (Knechtle et al, 2010a(Knechtle et al, , 2010b, body height (Knechtle et al, 2010a), body mass index (Knechtle et al, 2010a(Knechtle et al, , 2010b, percent body fat (Knechtle et al, 2010a(Knechtle et al, , 2010b, circumferences of limbs (Knechtle et al, 2010a(Knechtle et al, , 2010b) and thicknesses of skin-folds (Knechtle et al, 2010a) showed no correlation with race performance in ultra-endurance competitions, while previous experience (Knechtle et al, 2011b, Herbst et al, 2011, training and especially training intensity (Knechtle et al, 2010a(Knechtle et al, , 2010b on the other hand highly correlated with race performance.…”
Section: Introductionmentioning
confidence: 99%